SOLUTION TO OVERCOME THE BANKRUPTCY POTENTIAL OF ISLAMIC RURAL BANK IN INDONESIA - Devi, Abrista; Firmansyah, Irman (Journal of Islamic Monetary Economics and Finance, 2018)
This paper investigates the direct and indirect effect of macro and microeconomics variables toward financial distress by using efficiency variable as mediator. This research used time series and monthly-published report data of Islamic Banking Statistics and Macroeconomics data. The Springate Model is used to measure financial distress through s-score, while the Data Envelopment Analysis (DEA) approach is used to measure Islamic rural bank’s efficiency. The finding implies that the efficiency of Islamic rural bank in Indonesia is mainly caused by microeconomics variables where CAR and NPF directly have significant and negative effect on efficiency, while ROA and FDR directly have significant and positive effect on efficiency. The financial distress of Islamic rural bank in Indonesia is mainly caused by micro and macroeconomics variables where CAR and SIZE directly have significant and positive effect on financial distress score, while NPF and Exchange rate directly have significant and negative effect on efficiency. Efficiency is strongly having a role in mediating the effect of microeconomics variables toward financial distress score of Islamic rural bank